2021
DOI: 10.1002/pen.25684
|View full text |Cite
|
Sign up to set email alerts
|

Tuning morphology of siloxane bond‐based polybenzoxazines by controlling the sol–gel and curing processes

Abstract: Novel polybenzoxazine/polysilsesquioxane nanocomposites were synthesized with uniform and reproducible structural morphology, high Tg, and good thermal stability. Polysilsesquioxane was oriented in a nanometer‐size lamellar structure. Benzoxazine monomer based on silane (BA‐3aptms) was synthesized by reaction between bisphenol A, 3‐(trimethoxysilyl)propylamine, and paraformaldehyde in a 1:2:4 molar ratio. Four experimental conditions of the two stage sol–gel process for polysilsesquioxane were studied, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 60 publications
2
9
0
Order By: Relevance
“…This difference is associated with the high Si–O–Si bond dissociation energy (460 kJ/mol), giving excellent thermal resistance to materials. [ 49,54 ] In addition, it can be seen that the thermal stability of the materials is better under oxidizing atmosphere. According to previous investigations, [ 61 ] this behavior can be due to the formation of thermally stable chemical structures by oxidation reactions (decomposition products), such as quinone, amide, and imide bonds.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This difference is associated with the high Si–O–Si bond dissociation energy (460 kJ/mol), giving excellent thermal resistance to materials. [ 49,54 ] In addition, it can be seen that the thermal stability of the materials is better under oxidizing atmosphere. According to previous investigations, [ 61 ] this behavior can be due to the formation of thermally stable chemical structures by oxidation reactions (decomposition products), such as quinone, amide, and imide bonds.…”
Section: Resultsmentioning
confidence: 99%
“…In order to obtain the optimal conversion of siloxane structures in short reaction times the procedures were performed by following the procedure reported in previous study of Forchetti et al, reaching a compromise solution between the sol–gel process (hydrolysis and condensation reactions) and the thermally induced curing by oxazine‐ring opening. [ 49 ] The BA‐3aptms precursor synthesis procedure was divided into three stages. In the first stage, BA‐3aptms monomer and isopropanol (isopropanol/Si molar ratio = 4.5) were added to a flask provided with magnetic stirring at 30 °C to favor the hydrolysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This behavior is related to different siloxane‐bonded networks formed by the sol–gel process 32,33 . In our previous article, the influence of the sol–gel process conditions on the structural morphology and the thermal and mechanical performance of the hybrid benzoxazine resin was studied 34 . The results indicated that the morphology can be tailored by modifying the sol–gel conditions and thereby the thermal and mechanical properties of the final crosslinked materials.…”
Section: Introductionmentioning
confidence: 98%